2023
DOI: 10.3390/jof9010073
|View full text |Cite
|
Sign up to set email alerts
|

Fungi as a Source of Edible Proteins and Animal Feed

Abstract: It is expected that the world population will reach 9 billion by 2050. Thus, meat, dairy or plant-based protein sources will fail to meet global demand. New solutions must be offered to find innovative and alternative protein sources. As a natural gift, edible wild mushrooms growing in the wet and shadow places and can be picked by hand have been used as a food. From searching mushrooms in the forests and producing single cell proteins (SCP) in small scales to mega production, academia, United Nations Organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 147 publications
0
16
0
Order By: Relevance
“…Macroscopic filamentous fungi that form large fruiting bodies are known as mushrooms [ 107 ]. Edible mushrooms are the higher fungi in the Ascomycetes and Basidiomycetes classes [ 108 ]. Great attention was given to the polysaccharides produced by numerous fungi, especially mushrooms, because of their various biological properties, such as antioxidant, antimicrobial, and immunostimulant activities [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic filamentous fungi that form large fruiting bodies are known as mushrooms [ 107 ]. Edible mushrooms are the higher fungi in the Ascomycetes and Basidiomycetes classes [ 108 ]. Great attention was given to the polysaccharides produced by numerous fungi, especially mushrooms, because of their various biological properties, such as antioxidant, antimicrobial, and immunostimulant activities [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Edible mushrooms are known to have good quality proteins, high fiber content, large amounts of vitamins and minerals, lectins, and also bioactive compounds such as polysaccharides, β‐glucans and polyphenols (Amara & El‐Baky, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that Ab have significant medicinal properties, such as antitumor, antidiabetic, immunostimulatory, antioxidant, and antiviral effects due to the presence of those bioactive compounds (Amara & El‐Baky, 2023; Goyal et al, 2006; Ramos et al, 2019). Natural substances like mushrooms, garlic, or isolated ones as vitamin E (α‐tocopherol), and ascorbic acid (vitamin C) have been used since ancient times for the prevention and treatment of various pathologies (Chopra & Dhingra, 2021; Stojkovic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some fungi with high protein value have been produced by cell culture method and used as human food or animal feed. (Amara & El-Baky, 2023). Some fungi are used in the preparation of some special cheeses (Rokfort, Gorgonzola, Kamembert, mouldy cheese produced in Anatolia).…”
Section: Fungi (Mould and Yeasts)mentioning
confidence: 99%